2022
DOI: 10.1002/jgm.3409
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA MALAT1 promotes osteogenic differentiation through the miR‐217/AKT3 axis: A possible strategy to alleviate osteoporosis

Abstract: Background: Accumulating evidence demonstrates that long non-coding RNAs (lncRNAs) are associated with the development of osteoporosis. The present study aimed to investigate the effect of metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) on osteogenic differentiation in osteoporosis.Methods: MALAT1 levels were detected by a real-time polymerase chain reaction (RT-qPCR). Moreover, the levels of osteogenic differentiation-related factors (Bmp4, Col1a1 and Spp1) were measured by a RT-qPCR and weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
(59 reference statements)
0
11
0
Order By: Relevance
“…MALAT1 was found to be downregulated in patients with PMOP, and MALAT1 levels were negatively associated with severity of PMOP [ 33 ]. Song et al suggested that MALAT1 expression was suppressed in hindlimb unloading mice and simulated microgravity treated cells, and overexpression of MALAT1 alleviated osteoporosis through regulating miR-217/AKT3 axis [ 34 ]. Furthermore, the role of MALAT1 in promoting osteogenic differentiation has been reported in a variety of cells, such as human periodontal ligament stem cells [ 35 ], renal interstitial fibroblasts [ 36 ], and BMSCs [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…MALAT1 was found to be downregulated in patients with PMOP, and MALAT1 levels were negatively associated with severity of PMOP [ 33 ]. Song et al suggested that MALAT1 expression was suppressed in hindlimb unloading mice and simulated microgravity treated cells, and overexpression of MALAT1 alleviated osteoporosis through regulating miR-217/AKT3 axis [ 34 ]. Furthermore, the role of MALAT1 in promoting osteogenic differentiation has been reported in a variety of cells, such as human periodontal ligament stem cells [ 35 ], renal interstitial fibroblasts [ 36 ], and BMSCs [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…These hub genes are primarily involved in the processes of cell proliferation and differentiation (24)(25)(26)(27)(28)(29)(30)(31). Some genes are also reported to be involved in the formation of osteoclasts (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the lncRNAs-transcription factor (TF) feedback loops are identified. Specifically, lncRNAs and TFs may compose feedback loops to mediate osteoblast differentiation, due to that TFs can directly mediate the differentiation activity by binding to the DNA-regulatory elements of lncRNAs (37).…”
Section: The Roles Of Malat1 In Osteoporosismentioning
confidence: 99%
“…MALAT1 has been considered as a biomarker in OP and is related to osteogenic differentiation ( 38 ). During the culture period of human MSCs, the osteogenic differentiation is developed from day 1 to 14.…”
Section: The Roles Of Malat1 In Osteoporosismentioning
confidence: 99%
See 1 more Smart Citation